HIV viral load levels and CD4(+) cell counts of youth in 14 cities - Ellen, Jonathan M. (2014)
OBJECTIVES: To describe the HIV viral load and CD4(+) cell counts of youth (12–24 years) in 14 cities from March 2010 through November 2011. METHODS: Baseline HIV viral load and CD4(+) cell count data were electronically abstracted in a central location and in an anonymous manner through a random computer-generated coding system without any ability to link codes to individual cases. RESULTS: Among 1409 HIV reported cases, 852 participants had data on both viral load and CD4(+) cell counts. Of these youth, 34% had CD4(+) cell counts of 350 or less, 27% had cell counts from 351 to 500, and 39% had CD4(+) cell counts greater than 500. Youth whose transmission risk was male-to-male sexual contact had higher viral loads compared with youth whose transmission risk was perinatal or heterosexual contact. Greater than 30% of those who reported male-to-male sexual contact had viral loads greater than 50 000 copies, whereas less than 20% of heterosexual contact youth had viral loads greater than 50 000 copies. There were no differences noted in viral load by type of testing site. CONCLUSION: Most HIV-infected youth have CD4(+) cell counts and viral load levels associated with high rates of sexual transmission. Untreated, these youth may directly contribute to high rates of ongoing transmission. It is essential that any public health test and treat strategy place a strong emphasis on youth, particularly young MSM.